If I ever get out of here [compact disc, unabridged] : a novel with paintings - Gansworth, Eric. 1965- (Random House/Listening Library, 2014)
Seventh-grader Lewis "Shoe" Blake from the Tuscarora Reservation has a new friend, George Haddonfield from the local Air Force base, but in 1975 upstate New York there is a lot of tension and hatred between Native Americans and Whites--and Lewis is not sure that he can rely on friendship.